Can Scanning Technique Affecting Elementary Students’ Understanding In Solving Math Narrative Text? - Purnamasari, Nensi Desiana; Abduh, Muhammad (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research was dedicated to finding out the effect of scanning techniques on cognitive aspects, with a focus on mathematics narrative text for fourth grade students in a rural environment. In carrying out this research, the method used was quasi-experimental. The sample for carrying out this research included an experimental class consisting of 22 students, while the control class consisted of 22 students. After carrying out this research, it was found that the experimental class, which used the scanning technique when carrying out learning activities, obtained an average score of 84.6, which was higher than the control class, which did not use the scanning technique only 72.8. Apart from that, the value of the effect size (d) was also obtained, the amount of which was 0.74, where this was adjusted based on the results obtained from calculating the effect size using the calculation form in the form of Cohen's d. Then, from the effect size value obtained, interpret the influence of using scanning techniques, which falls into the medium category. So, this statement provides an indication of where a good effect was found after using the scanning technique regarding cognitive aspects of ability with a focus on math story questions intended for fourth grade students in a rural environment.